Regulation of outer space : international space law and the state - Cinelli, Claudia; Ferrazzani, Marco (Abingdon, Oxon [UK] ; New York, NY : Routledge ; Torino : G. Giappichelli Editore, 2025)
"This edited book focuses on how States should regulate activities in space and explores strategies to advance State responsible behaviour to ensure sustainable use and effective protection of outer space for peaceful purposes. The time seems ripe to bring international law into the space sustainability discourse. The concept of sustainable development was conceptualized by the 1987 Brundtland Report, Our Common Future. Today, as then, the overlap between the security, environmental and economic dimensions, including in terms of intra/inter-generational equity, is reflected within the current 'new space' era that is now 'our common future'. This edited book collects original theoretical and empirical contributions. It contributes to unpack the international outer space regulatory framework in the light of current trends and pressing challenges. This offers a unique perspective and guidance thus empowering regulatory strategies for stakeholders and end-users such as scholars, policy-makers, industry and society"--
Does using satellite data for sustainable development justifies unsustainable use of outer space? / Claudia Cinelli -- Sustainability and Corporate Social Responsibility (CSR) in outer space / Elena Cirkovic -- Business, human rights and international space law : filling the gaps of corporate accountability in the 'new space' / Chiara Macchi -- The principle of 'Common Heritage of (Hu)mankind' : its implementation in the light of the law of the sea and the law of outer space / Anne-Sophie Martin -- Rights without remedies? The role of arbitration in enforcing international space law for private parties / Laura Yvonne Zielinski -- National space laws and regulations stemming from international space law / Emanuela Maio -- Nuclear power sources in outer space for peaceful purposes : an evolving legal framework / Viviana Iavicoli -- Concluding remarks. Recognizing and addressing the challenge of interdisciplinary collaboration, design, and governance in sociotechnical systems / Katlyn M. Turner.
Keywords: Space law; Outer space -- Government policy; LAW / Air & Space; LAW / Environmental; LAW / International